2016
DOI: 10.1177/0363546516677548
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Factors Associated With Tackle-Related Injuries in South African Youth Rugby Union Players

Abstract: The relative risk of tackle-related injury was higher toward the end of matches. Incorrect technique may contribute to increased injury risk. Implementing recovery strategies between matches, training safe and effective techniques, and improving levels of conditioning may counter the negative effects of fatigue. These findings may assist stakeholders in youth rugby to formulate injury prevention strategies and may improve the preparation of field-side medical staff for managing tackle-related injuries at these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 60 publications
4
56
0
Order By: Relevance
“…Tacklers were significantly more likely to sustain concussion when they contacted with their head/neck as the first point of contact. Our finding is in line with the results of previous research on injury scenes using video records in rugby union 15,28) . It was suggested that tacklers had a higher risk of concussion if tacklers made contact with their head as the first contact point.…”
Section: Conflict Of Interestssupporting
confidence: 93%
“…Tacklers were significantly more likely to sustain concussion when they contacted with their head/neck as the first point of contact. Our finding is in line with the results of previous research on injury scenes using video records in rugby union 15,28) . It was suggested that tacklers had a higher risk of concussion if tacklers made contact with their head as the first contact point.…”
Section: Conflict Of Interestssupporting
confidence: 93%
“…World Rugby has implemented recent law changes, with a specific focus on reducing the risk of head injury during a tackle. Tackle technique features associated with tackle-related injury have been identified in adult professional11 and competitive under-18 players 12. However, to our knowledge, no targeted interventions and reassessment of injury incidence have been carried out based on these technical recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the presence or absence of a concussion, the newly identified characteristics might have been seen frequently in the concussed tacklers. Thus, the definition used in previous research 7,11,12 might have underestimated the characteristics related to the occurrence of concussions while the definition used in the present study may have been able to solve this problem. Although the present study revealed important data for the prevention of tackler-related concussion, as mentioned above, several limitations should be addressed.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 70%
“…These findings are in line with the results of previous research on the characteristics of tackles based on video records in rugby union. 7,11,12,19 However, the confidence intervals of these characteristics were fairly wide. It is considered that the numbers within the subgroup, tackles with or without a concussion, were not drastically different in comparison to that for other characteristics, and thus, the standard error was large.…”
Section: Factors Increasing the Likelihood Of The Tackler-related Cmentioning
confidence: 99%
See 1 more Smart Citation